Prognostic factors of vision loss after vitrectomy surgery among patients with proliferative diabetic retinopathy in Hospital Raja Perempuan Zainab II - Noor, Abdah Khairiah Che Md Noor (2018)
Background: Proliferative diabetic retinopathy (PDR) is one of the major cause of blindness throughout the world. Its development is primarily related to progressive retinal ischemia from diabetic retinopathy while its complications could lead to vision loss, tractional retinal detachment, and vitreous hemorrhage. Vitrectomy is the mainstay of treatment when sight threatening complications of PDR such as vitreous hemorrhage and tractional detachment develop. The aim of this study was to identify the prognostic factors of vision loss after vitrectomy surgery among PDR patients. Methods: A retrospective cohort study involving 164 patients diagnosed with PDR that underwent vitrectomy surgery from 1st January 2012 to 31st December 2016 and were followed up at Ophthalmology Clinic Hospital Raja Perempuan Zainab II. Visual acuity values were determined by the line that the patients can recognize based on a Snellen chart. The Minimum Angle of Resolution and subsequently its log value (LogMar) was obtained by dividing the denominator by numerator of the Snellen acuity value. Subjects were considered to have vision loss when the visual acuity post vitrectomy surgery dropped by 0.3 LogMar. Kaplan Meier was used to determine the median time to vision loss and Cox Proportional Hazard regression was used to identify the prognostic factors of vision. Statistical analysis was done using STATA 14. Results: The mean age of patients was 52.68 years (SD=10.32). The patients consisted of 47.6% male and 52.4% female. The overall median time or median probability of vision loss obtained for this study was 14.63 months (95% CI:11.51, 17.75). Patients with premorbid condition Ischemic Heart Disease (IHD) (Adjusted HR: 1.71, 95% CI: 1.06, 2.78) and post-operative Tractional Retinal Detachment (TRD) (Adjusted HR: 1.80, 95% CI: 1.16, 2.79) had a higher risk in having vision loss post vitrectomy after adjusting for other factors. Conclusion: Time to vision loss was influenced by premorbid condition of IHD and a complication of post-operative TRD. Median time or survival duration of vision loss was about 14 months in general and this suggest that patients should be followed up closely for at least this period of time, especially those with risk factors like IHD.